How has the field of immunogenic cell death in breast cancer evolved and impacted clinical practice over the past eleven years? - Yu-Long Deng; Bang-Teng Chi; Shang-Yi Lu; Dan-Dan Xiong; Rong-Quan He; Di-Yuan Qin; Wan-Ying Huang; Xia Yang; Gang Chen; Wei Peng; Jiayuan Luo (Human Vaccines & Immunotherapeutics)
This study elucidates the research landscape of immunogenic cell death (ICD) in breast cancer through a bibliometric analysis of 457 Web of Science articles. Contributions from China and the USA are particularly prominent, with notable international collaborations. Core journals such as Biomaterials published influential studies, while researchers like Huang Y made impactful contributions. High-frequency keyword analysis identified key research hotspots, including immunotherapy, the tumor microenvironment, and nanomedicine. The integration of chemotherapy with immunotherapy and the identification of key proteins have driven recent advancements. Fundamental research on immunotherapy, photodynamic therapy (PDT), and triple-negative breast cancer (TNBC) points to future trends and potential breakthroughs. This study offers a strategic overview of ICD in breast cancer, providing insights into clinical practice and guiding future research in the field.